Conducting Research in Palliative Care as Viewed by Interprofessional Care Teams: Insights from a Cross-Sectional Survey - Coralie Roux; Sophie Pautex; Federica Bianchi; Lisa Hentsch (Palliative Medicine Reports, 2025)
Introduction: Conducting studies in palliative care can be challenging. It has been highlighted that the interprofessional team may have their own reasons for not engaging in research projects. We aimed to identify barriers and facilitators to the involvement of palliative care team members in research projects. Method: We used a cross-sectional online survey with qualitative and quantitative components to identify barriers and facilitators encountered by palliative care health professionals. Participants were physicians, nurses, nurse assistants, physiotherapists, dieticians, and occupational therapists working in the Division of Palliative Medicine of the Geneva University Hospitals in Switzerland. Data were analyzed using descriptive statistics and content analysis for the open-ended questions. Results: A total of 107 questionnaires were sent, and 51 participants (48%) provided responses, of whom 75% expressed an interest in research, although only 47% had previously taken part in a research project. The most cited barriers were a lack of training on how to conduct studies, a lack of time, and a lack of funding. The main facilitators were the recognition that research enhances the quality of care and the belief that patients should be respected in their autonomy and given the opportunity to participate in research projects. Conclusion: The interprofessional palliative care team would benefit from time, funds, and training in order to enhance a research culture within the team. The establishment of an interprofessional network to guide and share experiences would also be a good way to promote this culture.